2000
DOI: 10.1679/aohc.63.199
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical Effects of Capsaicin on the Primary Afferent Neurons.

Abstract: Studies by N. JANCSO and his associates in the 1970's established that capsaicin in paprika exerts selective damage on nociceptive primary sensory neurons. The physiological and pharmacological aspects of capsaicin's effect have been repeatedly reviewed, but no report seems available concerning the neuroanatomical changes caused by capsaicin. This paper first reviews the neuroanatomical aspect of the lesion caused by capsaicin. Special attention is paid to quantitative estimations made by our group and others … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 76 publications
3
47
0
Order By: Relevance
“…The primary afferent neurons, of spinal and vagal origins, convey sensory information from the upper gastrointestinal tract to the central nervous system. A substantial number of these primary afferents, mainly of spinal origin, were shown to be immunoreactive to TRPV1 and called capsaicin-sensitive sensory neurons [12,14,15,23,30,31,33]. In this study, capsaicin transiently inhibited the vagally mediated esophageal muscle contractions.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The primary afferent neurons, of spinal and vagal origins, convey sensory information from the upper gastrointestinal tract to the central nervous system. A substantial number of these primary afferents, mainly of spinal origin, were shown to be immunoreactive to TRPV1 and called capsaicin-sensitive sensory neurons [12,14,15,23,30,31,33]. In this study, capsaicin transiently inhibited the vagally mediated esophageal muscle contractions.…”
Section: Discussionmentioning
confidence: 57%
“…Enteric neurons in the esophagus are contacted by primary afferents of spinal and vagal origin [19,20,25]. A substantial number of these primary afferents, mainly of spinal origin, were shown to be immunoreactive to the transient receptor potential ion channel of the vanilloid type 1 (TRPV1) and called capsaicin-sensitive sensory neurons [12,14,15,23,30,31,33]. These neurons can modulate intestinal motility by transferring signals from the gastrointestinal tract to the central nervous system and simultaneously releasing transmitters, in particular substance P (SP) and calcitonin generelated peptide (CGRP) that can influence the activity of intrinsic neurons [14,16].…”
mentioning
confidence: 99%
“…In the hereditary sensory and autonomic neuropathy type I, which has clinical manifestation of small fibres sensory loss, leading to cutaneous ulcers and spontaneous stress fractures around the second decade of life, severe lancinating pain is the main complaint. Thus, the hereditary small fibres sensory neuropathy is painful in adults, but not in neonates, a condition rekindling the effects of capsaicin treatment in neonates and adult mice [53,25]. Small sensory and autonomic fibres are affected in other hereditary diseases in which the genetic abnormality leads to accumulation of substances in or around small neurons of sensory and autonomic ganglia.…”
Section: Heredithary Neuropathiesmentioning
confidence: 99%
“…There have been numerous reports in the last two decades relating to the decrease of primary sensory neurons and their processes following neonatal capsaicin treatment (Hiura, 2000). In particular, a number of authors have reported the marked loss of corneal nerve or its terminal in rats and mice pretreated at birth with capsaicin (Fujita et Kawakami et al, 1996).…”
mentioning
confidence: 99%